Environment Friendly Minimum Quantity Lubrication Technique - Virdi, Roshan Lal (Asian Journal of Engineering and Applied Technology, 2018)
Lubricants are always important for the machining of materials for any industry. Large quantity of rational lubricants poses environment and health problems to the workers. Research is focused nowadays on to replace traditional fluids which are harmful to meet the striker laws of environment. Nanofluids can be the alternative if made with proper base oils to protect the environment and workers health. Nanofluids has the ability to transfer more heat with good lubrication effects. Environment friendly nanoparticles with vegetable oils as base fluid in Minimum Quantity Lubrication (MQL) technique can help the industries to eliminate traditional oils.